Experimental study of energy loss in OWC-type wave energy converters - Kwa, Kai Ghuang. (2012)
The ocean wave energy extraction has been researched for a considerable amount of time in order to provide a comprehensive solution over increasing worldwide energy demand. One of the most promising ocean wave energy devices is the oscillating water column (OWC) wave energy device. This report presents the foundation of laboratory project basis in experimenting and analysing the performance of a front wall configuration.